Theory and numerical modelling of parity-time symmetric structures for photonics - Phang, Sendy (2016)
This thesis presents the study of a relatively new class of photonic structures in-voking Parity-Time (PT)-symmetry. PT-symmetric structures in photonics, as a realisation of PT-symmetric Quantum Mechanics problems, are constructed by a judicious design of refractive index modulation which requires the real part of the refractive index to be an even function and the imaginary part of the refractive index to be an odd function in space. PT-symmetric structures in the form of Bragg gratings, coupled resonators and chain resonators are the main conﬁgurations studied in this thesis. These PT-symmetric structures feature a spontaneous symmetry breaking at which interesting wave behaviour such as an asymmetric response depending on the direction of the incident wave, unidirectional invisibility, simultaneous coherent-perfect absorber lasing and localised termination modes are observed; these behaviours are presented in this thesis. Theoretical and numerical studies of these PT-symmetric structures are undertaken which assume realistic material parameters,including material dispersion and material non-linearity. Moreover,in this thesis, potential applications of these PT-symmetric structures are explored.